2011
DOI: 10.1111/j.1751-7133.2011.00256.x
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Changes During Acute Heart Failure Treatment

Abstract: Introduction Biomarker changes may provide physicians with objective evidence of treatment efficacy in patients with acute decompensated heart failure (ADHF), and facilitate early hospital discharge. We hypothesize that MR-proADM, CT-pro-ET-1 and MR-proANP change during the first 24 hours of ADHF therapy. Methods Eligible subjects had an ED diagnosis of ADHF and fulfilled modified Framingham Criteria. Clinical data, serum, and plasma were collected at enrollment, 2–4 hours, and 12–24 hours after treatment. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
1
4
0
3
Order By: Relevance
“…Indeed, mR-proANP increases with exercise, a known stimulus for ANP secretion. Conversely, cardiac unloading through heart failure treatment reduces mR-proANP levels [23].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, mR-proANP increases with exercise, a known stimulus for ANP secretion. Conversely, cardiac unloading through heart failure treatment reduces mR-proANP levels [23].…”
Section: Discussionmentioning
confidence: 99%
“…13,15 However, there is a little information about the changes of central blood flow and condition of cardiovascular system in such patients. Together with echocardiac findings, plasma levels of proANP, a molecule which is one of the most undisputable markers of cardiovascular insufficiency, 49,50 were increased in patients with liver cirrhosis. Moreover, it was found that T-allele carriers had significantly higher proANP plasma level compared with GG-genotype carriers, which correlated with structural changes of the heart: increased LA diameter and LVMM and LVMMI in males.…”
Section: Discussionmentioning
confidence: 83%
“…En la presentación en la emergencia o UCI, por tanto, el nivel de PN (BNP, NT pro-BNP) debería medirse en todos los pacientes con disnea de inicio agudo y sospecha de ICA para ayudar a la diferenciación de causas no cardíacas de disnea (24) .…”
Section: Péptidos Natriuréticosunclassified